PENINGKATAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM PEMBELAJARAN IPA KELAS 3 SEMESTER 2 SD NEGERI GOGODALEM 01 KECAMATAN BRINGIN KABUPATEN SEMARANG TAHUN AJARAN 2018/ 2019 - Nurhayati Nurhayati (Universitas Ngudi Waluyo, 2020)
This type of research is Classroom Action Research. Sources of research data were obtained from grade 3 students with a total of 19 students consisting of 12 boys and 7 girls. From the results of observations, tests, and documentation, it is known that: the learning outcomes of third grade science students in Gogodalem 01 State Elementary School are still relatively low, this can be seen from the large number of students with natural science learning outcomes who do not meet the Minimum Mastery Criteria (KKM) that is, 65, this is indicated by the initial IPA value before the action of 19 students who scored more than KKM only 5 students or 26.32% students, while 14 students or 73.68% other students whose grades were still below KKM. After applying the jigsaw cooperative learning model, student learning outcomes also increased from pre-cycle conditions by 42.1%, then after being given action in the first cycle students who finished to 13 students or by 68.42% with an average value of 67 , 68. Then given the action in the second cycle of students who completed into 17 students or 89.47% with an average value of 77.37. This proves that the application of the jigsaw cooperative learning model in improving science learning outcomes in competency standards understands various ways of moving objects, their relationship to energy, and energy sources in class III students of Gogodalem State Elementary School 01, Bringin District, Semarang Regency in 2018/2019.